Impacts of Technological Disasters - Megan Donovan; Suzanna Smith; Heidi Radunovich; Michael Gutter (EDIS)
Technological disasters such as the Deepwater Horizon/BP oil spill can be stressful. This publication reports on the impacts of technological disasters and offers some guidelines for families that are dealing with stress related to the oil spill. This 4-page fact sheet was written by Megan Donovan, Suzanna Smith, Heidi Radunovich, and Michael Gutter, and published by the UF Department of Family Youth and Community Sciences, May 2011.